Late Danubian mitochondrial genomes shed light into the Neolithisation of Central Europe in the 5th millennium BC - Chyleński, Maciej; Juras, Anna; Ehler, Edvard; Malmström, Helena; Piontek, Janusz; Jakobsson, Mattias; Marciniak, Arkadiusz; Dabert, Miroslawa (BMC evolutionary biology, 2017)
BACKGROUND: Recent aDNA studies are progressively focusing on various Neolithic and Hunter - Gatherer (HG) populations, providing arguments in favor of major migrations accompanying European Neolithisation. The major focus was so far on the Linear Pottery Culture (LBK), which introduced the Neolithic way of life in Central Europe in the second half of 6th millennium BC. It is widely agreed that people of this culture were genetically different from local HGs and no genetic exchange is seen between the two groups. From the other hand some degree of resurgence of HGs genetic component is seen in late Neolithic groups belonging to the complex of the Funnel Beaker Cultures (TRB). Less attention is brought to various middle Neolithic cultures belonging to Late Danubian sequence which chronologically fall in between those two abovementioned groups. We suspected that genetic influx from HG to farming communities might have happened in Late Danubian cultures since archaeologists see extensive contacts between those two communities. RESULTS: Here we address this issue by presenting 5 complete mitochondrial genomes of various late Danubian individuals from modern-day Poland and combining it with available published data. Our data show that Late Danubian cultures are maternally closely related to Funnel Beaker groups instead of culturally similar LBK. CONCLUSIONS: We assume that it is an effect of the presence of individuals belonging to U5 haplogroup both in Late Danubians and the TRB. The U5 haplogroup is thought to be a typical for HGs of Europe and therefore we argue that it is an additional evidence of genetic exchange between farming and HG groups taking place at least as far back as in middle Neolithic, in the Late Danubian communities.
Keywords: mitochondriální DNA; DNA, Mitochondrial; Neolithic transition; U5 haplogroup; haplotypy; migrace lidstva; Ancient DNA; Poland; běloši; Europe; Haplotypes; White People; Genetics, Medical; genom mitochondriální; Evropa; Human Migration; Genome, Mitochondrial; lidé; Mitochondrial DNA; Humans; Danubian Neolithic; lékařská genetika; Polsko